(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The growing trend of the 4th Industrial Revolution has propelled the application of numerous technological approaches in the construction industry. Building information modeling (BIM), laser scanners, unmanned aerial vehicles (UAVs), and automated construction equipment are increasingly incorporated in the sector. The present study examined the application of 3D geospatial information technology in road construction in Edo state, Nigeria. The Global Navigation Satellite System (GNSS), static light detection and ranging (LiDAR), and UAV LiDAR were used to build 3D geospatial information of the study area effectively, and 3D designs were generated using the acquired data. A 3D design reflecting the actual terrain was created, and various sensors were installed on the construction equipment to conduct experiments on construction automation. The study concludes that construction automation has the advantage of knowing the design values and the site condition in real-time. The finding has implications for improving construction productivity for roads and many other construction works.